Comparison of perceived acquisition value sought by online second-hand and new goods shoppers. (9th July 2018) - Fernando, Angeline Gautami; Sivakumaran, Bharadhwaj; Suganthi, L.
Abstract : Purpose: Second-hand/used goods channels compete with existing traditional channels to satisfy consumers' needs that are unmet by traditional retail networks. However, most studies on online shopping have largely ignored online second-hand/used good purchases. This study aims to use Thaler's mental accounting model, principal–agent perspective and contamination theory to highlight the differences in the value sought by online new goods and second-hand shoppers. Design/methodology/approach: A conceptual framework linking perceived uncertainty, perceived acquisition value and e-loyalty was developed and tested using structural equation modelling. The moderating effects of product type (new vs second-hand) and frugality were also included. Findings: The paper found strong support for the model. Results showed that online second-hand shoppers were more uncertain and perceived lesser levels of acquisition value when compared to new goods shoppers. They were also less frugal. Online shoppers are also more likely to buy products with sensory attributes (experience goods) in new goods websites and products with non-sensory attributes (search goods) from second-hand websites. The authors recommend various ways in which managers can increase perceived value for the online shopper. Research limitations/implications: Future studies can extend this investigation by including transaction value or other hedonic values to verify their impact on acquisition value and e-loyalty. While the authors found support for the notion that consumers who buy used goods online are less frugal, there is some research that could point to the opposite. Hence, research can investigate this topic in depth in more countries to throw more light on this. Practical implications: To sustain themselves in a competitive online market, retailers need to understand the value sought by consumers. This study provides empirical evidence of the importance of acquisition value for new goods and second-hand shoppers. Originality/value: No recent research has compared the value sought by online second-hand and new goods shoppers. This study contributes to the understanding of the acquisition value perceived by consumers in online new goods and second-hand shopping channels.